Nanoparticles as a Novel Delivery Vehicle for Therapeutics Targeting Erectile Dysfunction - Han, George (2009)
INTRODUCTION: Nanoparticles represent a potential novel mechanism for transdermal delivery of erectogenic agents directly to the penis. AIM: To determine if nanoparticles encapsulating known erectogenic agents (tadalafil, sialorphin, and nitric oxide [NO]) can improve erectile function in a rat model of erectile dysfunction (ED) as a result of aging (the Sprague-Dawley retired breeder rat). METHODS: Nanoparticles encapsulating the erectogenic agents were applied as a gel to the glans and penile shaft of anesthetized Sprague-Dawley rats and the intracorporal pressure/blood pressure (ICP/BP) monitored for up to 2 hours with or without stimulation of the cavernous nerve. Control nanoparticles were made without encapsulating erectogenic agents and applied in a similar manner in separate experiments. RESULTS: Nanoparticles encapsulating NO caused spontaneous visible erections in the rat, with an average time of onset of 4.5 minutes, duration of 1.42 minutes, and ICP/BP of 0.67 ± 0.14. The sialorphin nanoparticles also caused visible spontaneous erections after an average of 4.5 minutes, with a duration of 8 minutes and ICP/BP ratio of 0.72 ± 0.13. The difference in the erectile response between groups of animals treated with NO or sialorphin nanoparticles was significantly different from the control group treated with empty nanoparticles (P < 0.05) Tadalafil nanoparticles showed a significant increase in the mean ICP/BP (0.737 ± 0.029) following stimulation of the cavernous nerve (4 mA) 1 hour after application of the nanoparticles with a visibly improved erectile response. CONCLUSIONS: Nanoparticles encapsulating three different erectogenic agents resulted in increased erectile function when applied to the penis of a rat model of ED. Nanoparticles represent a potential novel route for topical delivery of erectogenic agents which could improve the safety profile for existing orally administered drugs by avoiding effects of absorption and first-pass metabolism, and would be less hazardous than injection.